Developing Teacher Professionalism Through Academic Supervision Activities of School Principle - Fujiono Fujiono; Citra Siwi Hanayanti; A. Idun Suwarna; Rinovian Rais; Ahmad Ridani (Journal on Education, 2023)
The purpose of this research is to describe the development of teacher professionalism as a result of the principal's academic supervision activities. The research methodology employed is a qualitative method with a qualitative descriptive approach. Observation, interviews, and documentation studies were used as data gathering methods. Also, a qualitative analysis was performed while the activities of data reduction, data presentation, and conclusion-making were in progress. The findings of this investigation suggest that school principals as supervisors have attempted to develop the potential and competence of teachers through teacher certification program activities which are attended by most teachers. The coaching program carried out by school principals for teachers consists of academic supervision activities, training (education and training), workshops, work meetings, PKG (teacher performance assessment), PKB (continuous professional assessment), technical guidance, and seminars. The outcomes of the teacher academic supervision activities carried out by the school principal show that the teacher development program activities through academic supervision activities have been progressing well. The problem preventing the principal's academic supervision from being put into effect is the learning method which is still teacher-centered so that it is monotonous and students become passive. The principal's strategy for achieving effective academic supervision is to conduct class observations and assign assignments to the teacher so that the teacher's academic abilities can be seen.